Padang Restaurant Names in Surabaya: A Linguistic Anthropology - Wulansari, Dwi Windah (Language Circle: Journal of Language and Literature, 2020)
This study examines the naming of Padang restaurants in Surabaya. The results show that there are two strategies that business owners use in naming their Padang home businesses, namely by using convergence and divergence strategies. The choice of name related to the convergence strategy is the name of the owner; prayer and hope; place name; natural conditions; words that are allocated with food; words that reflect nationalism. Whereas the selection of names using the divergence strategy relates to the names of relatives, names of kings and respected people; place name; names related to togetherness and circumstances; and the name that is allocated with the taste of food. Semantically, the word used in naming Padang restaurants refers to a concept that describes the norms, values and outlook on life of the Minangkabau people.